Adjustable Sutures in Constant Exotropia - Fawad Rizvi, Munira Shakir, Zeeshan Kamil, Shakir Zafar, Syeda Aisha Bokhari (Pakistan Journal of Ophthalmology, 2018)
Purpose: To evaluate the use of adjustable sutures in constant exotropia. Material and Methods: The study was conducted in LRBT Free Base Eye Hospital Karachi from April 2010 to March 2011. This was a retrospective study of eighteen patients who were operated for strabismus by adjustable suture technique. Preoperative assessment and postoperative results, all were reviewed from hospital record. All patients included in this study were exotropic preoperatively. After the surgery, adjustment of sutures was done after the effect of anesthesia wore off. The main outcome measures were a need for reoperation, patients’ satisfaction with regard to final cosmetic appearance, and change in angle of deviation at the end of follow up. Follow up period was six months. Results: Eighteen eyes of eighteen patients who were operated for exotropia out of which 72.2% were male and 27.7% were female. Mean change in angle of deviation at the end of follow up was from 60.55 ± 11.75 PD to 15.22 ± 5.15 PD with a percentage change of 74.62% (p= 0.000).Sixteen out of eighteen (88.8%) patients were satisfied with their cosmetic appearance. Conclusions: Adjustment strabismus surgery is an easy, tolerable and effective surgery, and is recommended for patients who are cooperative.